Internet contre Greta Thunberg : une étude discursive et argumentative - Albin Wagener (Argumentation et Analyse du Discours, 2020)
Greta Thunberg, the champion of the school strike for climate, is well-known for her declarations at the COP24 or in front of various assemblies and parliaments. From the moment a member of parliament invited her to speak at the French National Assembly on Friday, July 23rd, 2019, with other French climatologists among whom Valérie Masson-Delmotte, many people have publicly produced negative comments and sceptical discourses about her. Such utterances have been published in French speaking media such as newspapers, magazines, pureplayers and blogs, to name but a few. In this context, I propose to examine how the opponents to the Swedish activist have structured their viewpoints within the discourses they produce, to study their opinions and counter-discourses, and to understand the argumentative structures underlying them.